Profil Kreativitas Siswa Dalam Pemecahan Masalah Visual-Spasial Matematika Ditinjau Dari Kecerdasan Logis Matematis Siswa SMAN 6 Mataram - Dwi Novitasari (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2017)
This study is explorative research with a qualitative approach, aims to reveal the profile of student's creativity in solving mathematics problems about visual-spatial problems based on logic mathematics intelligence. The subjects of the study were 4 students of SMAN 6 Mataram, 2 students with a high logic mathematics intelligence (KLT), and the other 2 students with a medium logic mathematics intelligence (KLS). Data were collected by conducting task analysis an interview, then analyzed by employing qualitative content analysis with a deductive approach. The result of the study reveals that 1) the students’ creativities in terms of product, the students with high logic mathematics (KLT) generally are better than the students’ with medium logic mathematics intelligence (KLS) in solving the same problem, 2) the students’ creativities in terms of the process: generating, planning, and producing, KLT using visual ability to imagine what will be they created first and then uses logic mathematics intelligence in solving the problem while KLS using mathematical logical intelligence first and then use the visual capabilities afterward to imagine what they will be created.